2010
DOI: 10.1111/j.1365-2249.2010.04203.x
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of p38 mitogen-activated protein kinase activation and proinflammatory cytokine production by mitogen-activated protein kinase inhibitors in inflammatory bowel disease

Abstract: SummaryCrohn's disease and ulcerative colitis are inflammatory bowel diseases (IBD) characterized by chronic relapsing mucosal inflammation. Tumour necrosis factor (TNF)-a, a known agonist of the mitogen-activated protein kinase (MAPK) pathway, is a key cytokine in this process. We aimed first to determine whether p38 MAPK is activated in IBD inflamed mucosa, and then studied the effect of four different p38a inhibitory compounds on MAPK phosphorylation and secretion of proinflammatory cytokines by IBD lamina … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 35 publications
(45 reference statements)
2
40
0
Order By: Relevance
“…Recent experiments have evidenced the importance of p38 MAPK in UC, since they have demonstrated the use of p38 MAPK inhibitors for abrogated colitis [13,35,36]. MAPKs regulate cytokine production in response to a variety of stimuli [37] and upregulate COX-2 and iNOS expression in intestinal Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Recent experiments have evidenced the importance of p38 MAPK in UC, since they have demonstrated the use of p38 MAPK inhibitors for abrogated colitis [13,35,36]. MAPKs regulate cytokine production in response to a variety of stimuli [37] and upregulate COX-2 and iNOS expression in intestinal Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The p38 kinase pathway is known to regulate wide-ranging proinflammatory responses, including stimulation of proinflammatory genes (36,37), induction of COX-2 (38), increases in iNOS expression (39), increases in adhesion molecule expression (40)(41)(42), and proliferation of inflammatory cells (43)(44)(45)(46). The p38 kinase is both upregulated and activated in intestinal tissue of patients with IBD, and inhibition of p38 kinase inhibits the secretion of inflammatory cytokines in intestinal tissue and in lamina propria mononuclear cells isolated from IBD patients (47,48). Previous studies have suggested that p38 kinase may also be involved in TJ barrier regulation (49).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using tissue-specific conditional knockouts of p38a mice showed the importance of this isoform in the inflammatory response, both in cultured macrophages in vitro (8) and for development of skin and gut inflammation in vivo (9,10). p38a also mediates inflammation in IBD; it is highly phosphorylated and active in the inflamed intestinal mucosa of patients with IBD (11,12). The role of p38a in colitis was confirmed in experimental mouse models, and p38a/bMAPK inhibitors have been tested in clinical trials (10,(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%